The ruins of Gorlan - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2005)
When fifteen-year-old Will is rejected by battleschool, he becomes the reluctant apprentice to the mysterious Ranger Halt, and winds up protecting the kingdom from danger.